ANALISIS STILISTIKA WACANA TERJEMAHAN RESMI NASKAH PRASASTI PLUMPUNGAN (KAJIAN HISTORIS) - Nikolic, Hristina (Kajian Linguistik dan Sastra, 2008)
This article mainly deals with the Plumpungan manuscript discourse, an ancient stone inscription found in the Salatiga area. The manuscript dates back to the 8th century and is one of the main historical sources of the Salatiga municipality. There is a tight connection involving the above mentioned inscription with the legitimacy of the Javanese court at that time, as well as with the monarch, who was seen as half- man, half-deity. The monarch drew on the labor of his subjects in maintaining reli- gious sites to ensure his place on earth, and in heaven. The Plumpungan manuscript was a âlegal documentâ used to reassure inhabitants of the area that the monarch is the legitimate ruler, and to prevent further revolt. The monarchâs subjects in the Salatiga area at the time were farmers disheartened with high taxes and the fear of volcanic eruptions, which later caused great migrations to East Java. Consequently, the mon- arch, using the Plumpungan manuscript as a medium, decreed that the Hampra vil- lage (present-day Salatiga) become a tax-free area due to the excellent care that its citizens provided for the religious sites, in addition to the obeisance shown to the monarch. It becomes clear, however, that all the way through the discourse analysis, the king wanted to ensure his legitimacy. Socio-historical context confirms that the monarch, Bhanu, was a successful ruler who held power over four regions, analogi- cally with Indra, the king of all deities. Discourse analysis is detained under three main dimensions, which is grammatical, lexical and contextual, unified from be- ginning to end in a particular style that reveals genuinely hidden meaning.Â Â Key words: manuscript, Plumpungan, kodikologi, dan analisis stilistika.Â